2013
DOI: 10.18433/j3q888
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP3A5 Genotypes on the Pharmacokinetics of Carbamazepine when used as Monotherapy or Co-Administered with Phenytoin, Phenobarbital or Valproic Acid in Thai Patients

Abstract: -Purpose:To determine the effects of CYP3A5 polymorphisms on carbamazepine (CBZ) pharmacokinetic parameters when CBZ is used either as monotherapy or co-administered with phenytoin (PHT), phenobarbital (PB) or valproic acid (VPA). Methods: Retrospective data were collected from an electronic database and medical records. Blood samples were obtained and drug concentrations analyzed as a part of routine therapeutic drug monitoring (TDM). Screening for wild-type CYP3A5*1 and CYP3A5*3 single nucleotide polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
3
11
0
2
Order By: Relevance
“…Thirty-eight percent of the patients received kidney allograft from a deceased donor. CYP3A5 distribution among donors in this study was comparable to other studies for the Asian population [22,23], in which CYP3A5*3/*3 (n = 29) was the most common genotype followed by *1/*3 (n = 15) and *1/*1 (n = 6) respectively.…”
Section: Resultssupporting
confidence: 85%
“…Thirty-eight percent of the patients received kidney allograft from a deceased donor. CYP3A5 distribution among donors in this study was comparable to other studies for the Asian population [22,23], in which CYP3A5*3/*3 (n = 29) was the most common genotype followed by *1/*3 (n = 15) and *1/*1 (n = 6) respectively.…”
Section: Resultssupporting
confidence: 85%
“…Two hundred and eleven studies not fulfilling the eligibility criteria were further excluded. Finally, a total of 86 studies were included in this review. These included 25, 24, 20 and 17 studies on CYP2C9 , CYP2C19 , CYP2D6 and CYP3A5 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, no association was observed between CYP3A5*3 genotypes with CBZ pharmacokinetic parameters in Caucasians [29]. A recent study on Thai patients indicated that CYP3A5 expressers showed lower CDR CBZ relative to CYP3A5 nonexpressers when CBZ was administrated in combination with an enzyme-inducing AED but not as monotherapy [44].…”
Section: Discussionmentioning
confidence: 98%